Cover Feature: Rapid Screening of Mechanistic Pathways for Oxygen‐Reduction Catalysts (ChemCatChem 3/2023). Issue 3 (8th February 2023) - Exner, Kai S.
Abstract : The Cover Feature illustrates that the volcano plot for the oxygen reduction reaction (ORR) is impacted by a plethora of different mechanistic descriptions, including the mononuclear, dissociative, OOH dissociation, and oxide mechanisms. In their Research Article, K. S. Exner introduces the adsorption free energy of the *OH intermediate as an efficient descriptor for rapid screening of ORR pathways. The novelty of the presented work constitutes the possibility of screening all possible mechanisms by volcano analyses to identify the energetically preferred one. The introduced procedure may support future DFT‐based studies so that the preferred pathway is not missed when modeling the four‐electron ORR by a binding‐energy approach. More information can be found in the Research Article by K. S. Exner .